Geographical distribution of the population in Syria and its reflection on State force - محمد, ياسر; غيثاء زوان (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This study examines the geographical distribution of the population in the Syrian Arab Republic and the factors affecting this distribution. It shows that the population of the Syrian Arab Republic is more than its main source. They are the justification for its composition and existence and the decisive element of its strength or vulnerability. It shows that the geographical distribution of the population in any region is a reflection of natural and human circumstances. These factors constitute the basis for their concentration or fragmentation and how this reflects the strength and development of the State in various respects. The importance of the geographical factors and their impact on the distribution of the population in Syria has been demonstrated by the fact that natural factors such as tactileness , climate, water resources and human factors are reflected in economic, social and political factors. This research has shown that there is a significant concentration of the population in specific areas, consisting of city centers, coastal areas and the capital city of Damascus, which confirms the weakness of the development currency or its decline in other areas. It therefore requires clear development plans and programmes in the less concentrated regions, thus achieving some balance in the distribution of the population and increasing the effectiveness of the population in building and strengthening of Syria.